2017
DOI: 10.3390/ijerph15010049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interprofessional Relationships from Nurses’ Perspective on the Decision-Making Capacity of Patients in a Clinical Setting

Abstract: Interprofessional relationships may impact the decision making of patients in a clinical setting. The objective of this study was to analyse the decision-making capabilities of patients from nurses’ perspectives of interprofessional relationships using Foucauldian ethics. This qualitative study was based on poststructuralist Foucault references with in-depth interviews of nurses working in internal medicine and specialties in a general hospital. The patients constantly appeared in the definition of teamwork, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
9
0
3
Order By: Relevance
“…The complex task of nursing documentation is often guided by the nursing process, a framework for solving patient care problems, and ensuring the provision of high-quality nursing care. Furthermore, this result was supported by results of Molina-Mula et al, (2018) which revealed that the majority of studied samples resulted in accepted level of nursing documentation quality.…”
Section: Discussionsupporting
confidence: 64%
“…The complex task of nursing documentation is often guided by the nursing process, a framework for solving patient care problems, and ensuring the provision of high-quality nursing care. Furthermore, this result was supported by results of Molina-Mula et al, (2018) which revealed that the majority of studied samples resulted in accepted level of nursing documentation quality.…”
Section: Discussionsupporting
confidence: 64%
“…On top of this, nurses are generally not encouraged, nor enabled to reflect on practice in order to generate new insights and nursing practice [35]. Molina-Mula et al [23], discuss the nursing profession as being the key to professional teamwork models, meeting the needs of patients and thereby increasing their personal decisionmaking capacity. However, it is possible that PCC is hindered by the level of professional autonomy, time and space afforded to nurses [57].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are the healthcare professionals who spend the most time with people and are therefore in a position to act as their advocates, with nursing staff managing the continuity of care [23]. This review seeks to investigate the meaning of person-centred nursing practice, and acts as a starting point for a wider study into the concept of PCC for people with long term conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a majority of nurses in one study expressed the belief that an egalitarian model, in which nurses’ opinions are frequently sought, and in which patients and family members are not excluded from decision-making, is vital in enhancing communication within the clinical contexts. This belief sometimes brings nurses into conflict with physicians who believe themselves to be the experts, and upon whom others (including nurses) must depend (Molina-Mula et al, 2017 ). Communication difficulties amongst health professionals can also lead to poor communication with patients and family members.…”
Section: Resultsmentioning
confidence: 99%